Two Decades of Global Progress in Authorized Advanced Therapy Medicinal Products: An Emerging Revolution in Therapeutic Strategies - Ramezankhani, Roya; Torabi, Shukoofeh; Minaei, Neda; Madani, Hoda; Rezaeiani, Siamak; Hassani, Seyedeh Nafiseh; Gee, Adrian P.; Dominici, Massimo; Silva, Daniela Nascimento; Baharvand, Hossein; Hajizadeh-Saffar, Ensiyeh (Frontiers in Cell and Developmental Biology, 2020)
The introduction of advanced therapy medicinal products (ATMPs) to the global pharma market has been revolutionizing the pharmaceutical industry and has opened new routes for treating various types of cancers and incurable diseases. In the past two decades, a noticeable part of clinical practices has been devoting progressively to these products. The first step to develop such an ATMP product is to be familiar with other approved products to obtain a general view about this industry trend. The present paper depicts an overall perspective of approved ATMPs in different countries, while reflecting the degree of their success in a clinical point of view and highlighting their main safety issues and also related market size as a whole. In this regard, published articles regarding safety, efficacy, and market size of approved ATMPs were reviewed using the search engines PubMed, Scopus, and Google Scholar. For some products which the related papers were not available, data on the relevant company website were referenced. In this descriptive study, we have introduced and classified approved cell, gene, and tissue engineering-based products by different regulatory agencies, along with their characteristics, manufacturer, indication, approval date, related regulatory agency, dosage, product description, price and published data about their safety and efficacy. In addition, to gain insights about the commercial situation of each product, we have gathered accessible sale reports and market size information that pertain to some of these products.